Could trade agreements help address the wicked problem of cross-border disinformation? - Susan Ariel Aaronson (Centre for International Governance Innovation (CIGI), 2021)
Whether produced domestically or internationally, disinformation is a "wicked" problem that has global impacts. Although trade agreements contain measures that address cross-border disinformation, domestically created disinformation remains out of their reach. This paper looks at how policy makers can use trade agreements to mitigate disinformation and spam while implementing financial and trade sanctions against entities and countries that engage in disseminating cross-border disinformation. Developed and developing countries will need to work together to solve this global problem.
Keywords: 330